Differential arousal and neural engagement for angry and fearful faces: a combined pupillometric and fMRI study - Wende, Kim C.; Kessler, Roman; Rusch, Kristin M.; Sommer, Jens; Jansen, Andreas (Frontiers in Human Neuroscience, 2026)
IntroductionUnderstanding how emotions are encoded at the neural level remains a central challenge in human neuroscience. Facial expressions are among the most powerful and frequently used stimuli to study emotion processing. Face perception itself is a complex function supported by a core network—including bilateral occipito-fusiform and superior temporal regions—and an extended network involving anterior structures such as the bilateral amygdalae. However, previous findings on how emotional content modulates these networks have been inconsistent.MethodsTo disentangle perceptual and affective components of face emotion processing, we combined high-frequency pupillometry with functional magnetic resonance imaging (fMRI). Pupillary dilation serves as a sensitive index of two distinct processes: perceptual load, reflecting the informational complexity of a face, and arousal, indicating its immediate sensory impact. In our study, 25 participants (13 female) viewed faces expressing anger, fear, happiness, or neutrality as well as luminance-matched houses serving as control stimuli. A one-back task unrelated to emotion masked the true experimental purpose.ResultsRelative to houses, faces elicited stronger pupillary dilations as well as enhanced blood-oxygen-level-dependent (BOLD) activity in bilateral occipital and fusiform cortices as well as in both amygdalae. Among facial expressions, angry faces evoked the largest pupillary dilations, while fearful faces elicited the strongest neural responses within a right-lateralized network centered on the superior temporal sulcus (rSTS). Across all faces>houses (conjunction minimum-statistic inference), pupil size correlated positively with BOLD activity in the right fusiform gyrus (rFFG), left inferior occipital gyrus (lIOG), bilateral calcarine cortex, and bilateral lingual gyrus.DiscussionThese findings indicate that emotional faces impose a higher perceptual load than matched control stimuli, engaging a distributed network spanning early visual and attention-related areas. In conclusion, our results suggest that emotional quality is specified early in the perceptual process, with divergent pupillary and neural signatures separating arousal-driven threat responses (anger) from socially complex alarm cues (fear).